Variability in the perception and application of force used in IVC filter retrievals among interventional radiologists. Issue 1 (February 2022) - Chan, T.Y.; Shaikh, U.; England, A.; McWilliams, R.G.
Abstract: Introduction: A long dwell time is associated with higher inferior vena cava (IVC) filter retrieval complication rates. Manufacturers advise that "excessive force should not be used" during filter retrieval; however, the term "excessive" is subjective and is likely to lead to variability amongst operators. The aims of this study were to 1) ascertain what interventional radiologists consider to be excessive force during filter retrieval and 2) to understand the variability in interventional radiologists' perception of force. Methods: The authors recruited interventional radiologists to perform a benchtop simulated filter retrieval. Participants were invited to pull on a modified force tester attached to a Gunther Tulip filter retrieval set (GTRS). The participants were asked to pull as if they were retrieving an IVC filter and stop when they felt it was clinically unsafe to apply greater force. They were then asked to replicate forces of 10N and 50N, respectively. Each of the three tasks was completed three times. Data were obtained on the clinical experience of the participants with specific questions focusing on their filter retrieval practices. Results: The range of maximum forces applied during filter retrieval varied between 0.8 and 79.8N. When asked to replicate 10N and 50N, for attempt-1, the median forces produced were 23.5N and 38.1N, respectively. A trend analysis showed that those who overestimate 10N are more likely to apply a greater overall maximum force (rs  = 0.622; P < 0.001). Conclusion: There is wide variation in what interventional radiologists consider to be the maximum safe force to apply during IVC filter retrieval. Implications for practice: Manufacturers and operators should consider methods in which only a safe range of forces can be applied during an IVC filter retrieval. Operators may wish to undertake 'personal' force calibration as part of training in interventional radiology.